Front Cover: Design, development and optimization of new high performance thin‐layer chromatography method for quantitation of Retapamulin in pharmaceutical formulation: Application of design of experiment. Issue 4 (16th April 2020) - Patel, Rashmin; Patel, Nishant; Patel, Mrunali
Abstract : DOI: 10.1002/sscp.201900107 The cover picture shows the design, development, optimization, validation and application cycle for a new HPTLC method for quantitation of Retapamulin in pure powder, cream and microemulsion formulations by means of design of experiment approach. Surface response plot explains the effect of factors on Rf value, 3D overlay of HPTLC densitogram represents the calibration bands and chromatograms shows quantitative application of HPTLC method for estimation of Retapamulin.